Quantifying the Impact of Research for Tenure and Promotion in Family and Consumer Sciences. (March 2016) - Delgadillo, Lucy M.
Abstract : This paper provides an overview of different metrics to quantify the impact of scholarly work in Family and Consumer Sciences, for scholars involved in the tenure and promotion process. Even though each institution will have their set of rules, most professors in university settings are increasingly subjected to monitoring and evaluation of their research outputs. This paper describes several metrics that are valid and reliable including age of the journal, acceptance rate, ISI impact factors, the SJR journal ranking, and the journals' h‐index. Two author‐level metrics, the Hirsh h‐index and the HLA index, are described. In the remainder of the article, three other quantifiable criteria are included.